Non-Muslim Customer Preferences towards Islamic Banks in Semarang - Nur Baethi Hariyana; Laily Dwi Arsyianti (AL-MUZARA'AH, 2019)
The prohibition of riba is applied by all religions. Islamic banking has a potential to attract non-Muslim customers. Semarang, both the regency and the city, has the largest non-Muslim population in Central Java. Currently, the number customers using Islamic banks has reached 22 million in 2017. This nominal can be escalated by elaborating non-Muslim preference towards Islamic banks. Therefore, this study aims to determine the factors that influence the preferences of non-Muslim customers towards Islamic banks in Semarang regency and the city. There are 120 respondents who have been interviewed, consisting of 60 respondents are Islamic bank customers and 60 respondents are conventional bank customers. They are selected based on non-probability sampling technique. Logistic regression method is employed to analyze the data. Results show the preferences of non-Muslim customers using Islamic banks are knowledge, profit sharing, religions, administrative profit, and income. Islamic banks can target non-Muslim customers through actively involved in disseminating Islamic financial products.